Implementation of phase controlled impact device for enhancement of frequency response function in operational modal testing - Lim, Hong Cheet; Ong, Zhi Chao; Brandt, Anders (Elsevier, 2018)
This paper studies how to enhance frequency response function (FRF) estimation in the presence of harmonic disturbances during operational modal testing. A novel technique which utilizes impact-synchronous time averaging (ISTA) called impact-synchronous modal analysis (ISMA) was introduced where modal analysis can be performed in the presence of ambient forces. The phase angle information of the harmonic signal at the impact events is shown to be a key factor in enhancing the effectiveness of this technique. However, lack of knowledge and control of impact with respect to the phase angle of the disturbances using conventional impact hammer in ISMA has limited the effectiveness and practicality of this novel technique. A portable and automated phase controlled impact device is introduced in the effort to eliminate non-synchronous components with minimal possible impacts applied. This device makes use of the feeding phase angle information of responses from the cyclic load back to the device and imparts the impact at the correct time/phase which is always non-synchronous with respect to the phase of response from cyclic load. A reduced number of averages thereby expedite the overall modal testing procedure, an improved of FRF estimation and a good correlation of modal extraction data with benchmark data shown in this study has highlighted the advantages of ISTA using the proposed device.